PERAN PENYULUH PERTANIAN DALAM MENINGKATKAN PENDAPATAN USAHATANI PADI SAWAH DI DESA OLOBOJU KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Lusiana, Lusiana; Laapo, Alimuddin; Howara, Dafina (AGROTEKBIS, 2018)
This study aims to analyze the role of agricultural extansion and farming income of Rice in Oloboju village, Subdistrict of Sigi Biromaru, Sigi Regency, during May to August, 2016. The location determining of this study was determined by purposive sampling. The number of respondents is 30 people who often follow counseling. Collecting data in this study consisted of primary data and secondary data. Analysis of the data used is the method of Chi Square and revenue analysis. The results of this study indicated that the role of agricultural extension educator components such as supervising of farmers so far so good. This is demonstrated by > The role of extension in terms of supervising the farmers (9.27)> (5.99),andThe facilitator (12.17)> (5.99). Keywords : Rice Farming Income, The Role Of Agriculture.